Cardiovascular mortality associated with testosterone therapy in cisgender women and transgender men: a systematic review - Viana, Diogo Pinto da Costa; Câmara, Lucas Caseri; Alto, Lucio de Sousa Monte (Frontiers in Endocrinology, 2026)
BackgroundTestosterone therapy is increasingly prescribed in cisgender women for sexual and metabolic indications and constitutes the cornerstone of gender-affirming hormone therapy in transgender men. However, the nature and certainty of cardiovascular safety evidence supporting testosterone use differ across clinical contexts.ObjectiveTo synthesize the available evidence on cardiovascular mortality associated with testosterone therapy in cisgender women and transgender men, with specific attention to study design, duration of follow up, and certainty of evidence. This review does not aim to directly compare cardiovascular risk between populations.MethodsThis systematic review was conducted in accordance with the PRISMA 2020 guidelines and prospectively registered in PROSPERO (CRD420251009443). Randomized controlled trials evaluating transdermal testosterone therapy in cisgender women and observational cohort studies assessing testosterone therapy in transgender men were included. Risk of bias was assessed using the Cochrane RoB 2.0 tool and the Newcastle Ottawa Scale, and certainty of evidence was evaluated using the GRADE framework. Due to substantial clinical and methodological heterogeneity, quantitative meta-analysis was not performed.ResultsThirteen randomized controlled trials involving 2, 628 cisgender women receiving transdermal testosterone for periods ranging from 8 to 52 weeks reported no cardiovascular deaths. Thirteen observational cohort studies including 7, 837 transgender men receiving long term testosterone therapy reported 34 cardiovascular deaths, corresponding to an incidence rate of 1.81 per 1, 000 person years. The certainty of evidence was rated as moderate for short term outcomes in cisgender women and low to very low for long term cardiovascular outcomes in transgender men.ConclusionsThe available evidence on cardiovascular mortality associated with testosterone therapy differs substantially between cisgender women and transgender men, primarily reflecting differences in study design, follow up duration, and certainty of evidence rather than definitive conclusions regarding comparative cardiovascular risk. The absence of cardiovascular deaths in short-term randomized trials does not allow inference regarding long term cardiovascular safety, highlighting the need for adequately powered studies with extended follow-up and standardized outcome definitions.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251009443.